2007
DOI: 10.1016/j.icarus.2007.03.031
|View full text |Cite
|
Sign up to set email alerts
|

A survey of debris trails from short-period comets

Abstract: We observed 34 comets using the 24 micron camera on the Spitzer Space Telescope. Each image contains the nucleus and covers at least 10^6 km of each comet's orbit. Debris trails due to mm-sized or larger particles were found along the orbits of 27 comets; 4 comets had small-particle dust tails and a viewing geometry that made debris trails impossible to distinguish; and only 3 had no debris trail despite favorable observing conditions. There are now 30 Jupiter-family comets with known debris trails, of which 2… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
124
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(133 citation statements)
references
References 58 publications
7
124
0
Order By: Relevance
“…(3) The existence of large compact dust in the preimpact T1 coma has been reported by many researchers (Sykes & Walker 1992;Farnham et al 2007;Reach, Kelley, & Sykes 2007). The existence of such large dust in the preimpact T1 is consistent with the standard model, because the dust mantle formation depletes only fluffy aggregates.…”
Section: Introductionsupporting
confidence: 73%
“…(3) The existence of large compact dust in the preimpact T1 coma has been reported by many researchers (Sykes & Walker 1992;Farnham et al 2007;Reach, Kelley, & Sykes 2007). The existence of such large dust in the preimpact T1 is consistent with the standard model, because the dust mantle formation depletes only fluffy aggregates.…”
Section: Introductionsupporting
confidence: 73%
“…Thus, the observed anti-tail can possibly be considered as the inner part of a trail, a term usually used to describe the distribution of very large particles trailing behind the nucleus of short period comets (Sykes et al, 2004;Reach et al, 2007;Agarwal et al, 2007). Here we observe it in a long period comet.…”
supporting
confidence: 56%
“…Moreno et al (2008) studied the morphology of the dust cloud in terms of the dynamics of the particles, and found that >600 μm particles, which are much less sensitive to radiation pressure than micrometersized or smaller particles, could be ejected by the outburst. Evidence of such large particles is found to be ubiquitous in in situ observations (McDonnell et al 1986;Tuzzolino et al 2003), by the remote sensing observations of dust tail (Fulle 2004;Moreno 2009;Watanabe et al 1990) and dust trail Ishiguro 2008;Sarugaku et al 2007;Reach et al 2000Reach et al , 2007Kelley et al 2008), sub-millimeter and millimeter observations (Jewitt & Matthews 1997;Altenhoff et al 1999). As a result of these studies, we found that the power index of the size distribution of almost all comets would be in the range of −4 and −3 (Fulle 2004).…”
Section: Mass Erosionmentioning
confidence: 97%